Mekanisme Hamburan Defek Statis Dan Vibrasi Termal Terhadap Mobilitas Elektron Pada Film Tipis GaN - Rusdiana, Dadi; Hasanah, Lilik; Suhendi, Endi (BERKALA FISIKA, 2010)
Electrons Mobility in GaN thin films has been determined for temperature variation using approach method to the relaxation time due to the influence of static defect scattering and thermal vibrations. The simulation results show that electron mobility is strongly influenced by environmental temperature, except for the scattering of neutral impuritas type that does not affect the value of the charge carrier mobility even though the external temperature was varied. Â  Keywords: Electrons Mobility, defect static, thermal vibration